INNOVATIVE TECHNOLOGY FOR THE TREATMENT OF COGNITIVE DISORDERS - Yakushin, M A; Karpova, O V; Kabaeva, E N; Arseenkova, O Yu; Vorobeva, A V; Gabrielyan, A R (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2024)
The authors digitized therapeutic factors used in the treatment of various forms of cognitive disorders, including dementia, with the subsequent development of a medical information system «Diagnosis and treatment of cognitive disorders». The medical information system «Diagnosis and treatment of cognitive disorders» was created on the basis of the 1C platform, supplemented by the module «Treatment of cognitive disorders», focused on supporting medical decision-making when choosing therapeutic factors for patients with cognitive disorders. It is planned to use this module in the complex activities of memory impairment classrooms.